Analysis of Intervening Variables of New Product Performance affected by Tacit Knowledge and Strategic Flexibility - Nizar Alam Hamdani; Muhammad Ridwan; Galih Abdul Fatah Maulani; Intan Permana (Universitas Mercu Buana, 2022)
Objectives: Global Innovation Index revealed that the innovation performance of Indonesia is relatively poor compared to several ASEAN countries. The lowest indicator of innovation performance is related to business sophistication. In business activities, some experts identify innovation as the key factor in company competitiveness. The author plans to analyze product innovation, innovation processes, and organizational innovations as intervening variables.Methodology: This study is causal research with a 95% confidence interval in collecting and constructing data structures to evaluate the cause-and-effect relationship of the variables. The primary data was obtained through a survey of 90 small-scale leather apparel companies in Indonesia. Subsequently, the data was analyzed using a structural equation model and multiple.Finding: Compared to the previous studies, the results of this study indicated a novelty, product innovation, and process innovation can be intervening variables if there is strategic flexibility as exogenous variables and new product performance. To improve new product performance, every leather apparel industry in Indonesia must first increase tacit knowledge, strategic flexibility, product innovation, and process innovation.Conclusion: Based on the findings, the researcher suggests further research to examine the path analysis research framework are exogenous variables (strategic flexibility and tacit knowledge), endogenous variables (organizational innovation and new product performance), and intervening variables (product innovation and process innovation).